Role of universities in innovation - Dunbar, Rod (New Zealand Science Review, 2011)
​Universities exist to innovate – and to train innovators. Sometimes the discoveries emanating from universities have direct economic value through their value in industry, while sometimes the value is to society or humanity without any apparent direct impact on our economy. Governments and their advisors continue to fret about whether universities focus sufficiently on eco-nomic outputs, as if these are somehow opposed to intellectual pursuits. Yet there is plenty of support for the concept that the intellectual and the economic are inextricably linked – that the greatest economic gains any country can make in a competitive world depend on deep investigation of difficult problems. The key to unlocking the value in university innovation is presumably then to ensure that universities are well linked to industry, while enabling the universities to do what they do best.